The Dynamics of the Prosperous Justice Party's Strategy in the Depok City Regional Elections Across Four Periods (2005-2020) - Felix Marshall Jotham; Aniqotul Ummah (Journal of Law, Politic and Humanities, 2025)
This article explores the dynamics of the political strategy of the Prosperous Justice Party (PKS) in the Depok City Regional Head Election (Pilkada) during the 2005-2020 period. The focus of this study is to analyze the strategy of nominating mayors and deputy mayors by PKS, which managed to maintain power for almost 20 years, spanning four consecutive terms. Depok City became a significant stronghold for PKS, demonstrating the party's dominance through strategic adaptations over time. This research employs a descriptive qualitative approach, using campaign strategy indicators to evaluate PKS's success in the Depok City Pilkada. The main objectives of the study are to understand the evolution of PKS's strategy, identify the strategic steps taken, and explore the key factors that influenced the party's success in winning the Pilkada. The results reveal a gradual evolution in PKS's strategy. In the 2005 Pilkada, the party relied on conventional approaches such as grassroots networks and social activities. However, with technological advancements, PKS began adopting digital campaigns in subsequent elections. This transformation became evident in the 2015 and 2020 regional elections, where social media was used extensively to engage young voters and the urban middle class. The findings highlight that strategic adaptation, internal unity, and the ability to address local issues were key to PKS's dominance in Depok. The relationship between PKS and Depok City reflects a complex political dynamic, where the party successfully integrated traditional and modern campaign strategies to maintain its power. This research underscores the importance of adaptation, solidarity, and innovation in local political competition, which were the determining factors in PKS's success in the Depok City Regional Election from 2005 to 2020.